2004
DOI: 10.1097/00003465-200405000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Solutions in Critical Care Units

Abstract: The increasing complexity and acuity of the patient population at a southwest United States medical center was a catalyst in updating, revising, and distributing a current extravasation guideline document to caregivers. The guidelines provide information on initial treatment for nurses and the process for documentation and tracking of extravasations. The authors describe how a synthesis of the Nursing and Pharmacy partnership at Banner Good Samaritan Medical Center resulted in the creation of current extravasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Examples include a ''critical care bug team'' implemented to decrease the incidence of ventilator-associated pneumonias 336 and a ''rock and roll'' critical care program developed to prevent complications from immobility. 337 Administrators have relied upon CNSs to develop researchbased protocols, 229,338-347 clinical pathways, 348,349 guidelines, 278,[350][351][352][353][354][355][356] and policies [357][358][359][360][361][362][363][364][365][366] in their institutions. For instance, CNSs have championed policy changes related to assessment and treatment of pain.…”
Section: Second Substantive Area: Educate and Support Interdisciplinamentioning
confidence: 99%
“…Examples include a ''critical care bug team'' implemented to decrease the incidence of ventilator-associated pneumonias 336 and a ''rock and roll'' critical care program developed to prevent complications from immobility. 337 Administrators have relied upon CNSs to develop researchbased protocols, 229,338-347 clinical pathways, 348,349 guidelines, 278,[350][351][352][353][354][355][356] and policies [357][358][359][360][361][362][363][364][365][366] in their institutions. For instance, CNSs have championed policy changes related to assessment and treatment of pain.…”
Section: Second Substantive Area: Educate and Support Interdisciplinamentioning
confidence: 99%
“…17,23,24) Notably, several clinical case reports have shown that extravasation of less tissue invasive agents dissolved in acidic solutions, such as vancomycin (pH 4.0), doxycycline (pH 1.8-3.3), and amiodarone (pH 3.5-4.5), also induces skin lesions. [25][26][27] However, the effect of acidic pH on extravasation injury may be negligible, as in this study both pH 3.0 and pH 5.0 saline solutions did not induce skin lesions. Thus, the severity of injury induced by extravasated vasopressors might be determined mostly by their strength of vasoconstriction activity, rather than acidity.…”
Section: Discussionmentioning
confidence: 48%
“…Extravasation guidelines specifically cite vancomycin as a potential cause, recommending the use of cold compress in the event of extravasation. [15] Hadaway and Chamallas review appropriate vancomycin administration and make clear that vancomycin will cause tissue damage if it escapes the vein to the subcutaneous tissue. [16] While common admixtures of vancomycin are isotonic, the acidic pH warrants a need for infusion through a central venous catheter, despite distinct recommendations from the package insert.…”
Section: Discussionmentioning
confidence: 99%
“…[17] With no clear evidence-based vancomycin extravasation management in the literature, certain aspects of vesicant extravasation from chemotherapy guidelines and basic wound care were extrapolated with this patient. [15,18] We applied cold compresses to the extravasated area for the 24 hours. We also applied standard gauze open dressings with frequent changes and silver sulfadiazine 1% to the wound.…”
Section: Discussionmentioning
confidence: 99%